Re-contextualising advertising through re-creation: the recycling and translation of advertisements in the context of the COVID-19 pandemic - Cantarero-Muñoz, María (Universidade do Porto. Faculdade de Letras, 2022)
The COVID-19 pandemic completely reconfigured the semiotic landscape. When the crisis was at its height, a whole series of words, images and sounds (or their absence) became representative symbols of the context we found ourselves in, not only in the media, but also in public and private spaces. This article analyses how these semiotic systems were renegotiated in order to acquire new meanings in the context of the COVID-19 pandemic. It takes as a case study two Coca-Cola brand advertisements based on the same creative idea, which circulated in 2002 and 2020 respectively. Through a comparative analysis of the elements that make up each version of this multimodal text, it shows how the original advertisement was semiotically translated in order to adapt it to the needs of a new target context (the pandemic situation). We conclude that concepts drawn from intersemiotic and audiovisual translation studies can help shed light on these processes of recontextualization and meaning reconstruction in the case of multimodal texts.
Keywords: Semiótica y televisión; Advertising Translation; Multimodal Translation; Meaning Remaking; Intersemiotic Translation